Characterization of synovial fluid from periprosthetic infection in revision total joint arthroplasty by single‐molecule microscopy. Issue 6 (6th January 2020) - Kohlhof, Hendrik; Fröschen, Frank S.; Randau, Thomas M.; Hischebeth, Gunnar; Kehrer, Michael; Wirtz, Dieter C.; Schildberg, Frank A.; Kaminski, Tim P.
Abstract: Periprosthetic joint infection is among the most common and severe complications in total joint arthroplasty. Today, a combination of different methods is used for diagnosis because no single method with sufficient sensitivity and specificity is available. In this study, we explored the usability of single‐molecule microscopy to characterize synovial fluid samples from periprosthetic joint infections. Patients ( n  = 27) that needed revision arthroplasty underwent the routine diagnostic procedures for periprosthetic joint infection of the University Hospital in Bonn. Additionally, the diffusion rate of two probes, dextran and hyaluronan, was measured in small volumes of periprosthetic synovial fluid samples using single‐molecule microscopy. To evaluate the suitability of single‐molecule microscopy to detect PJI the AUC for both markers was calculated. The diffusion rate of hyaluronan in periprosthetic synovial fluid from patients with septic loosening was faster than in samples from patients with aseptic loosening. Single‐molecule microscopy showed excellent diagnostic performance, with an area under the receiver operating characteristic curve of 0.93, and allowed the detection of periprosthetic joint infection in patients that would be challenging to diagnose with current methods. For the first time, single‐molecule microscopy was used to detect periprosthetic joint infection. Our results are encouraging to study the value of single‐molecule microscopy in a larger patient cohort. The speed and accuracy of single‐molecule microscopy can be used to further characterize synovial fluid, potentially allowing intraoperative diagnosis of periprosthetic joint infections in the future.